Desain Pembelajaran yang Inspiratif dan Pengembangan Kurikulum yang Responsif bagi Kompetensi Pendidik - Hasni, Walidatil; Aprima, Septi Gia; Fadriati, Fadriati (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to explore an in-depth understanding of curriculum development, learning design, and educator competencies in the context of education in the era of independent learning. Qualitative research methods are used to gain a comprehensive understanding through in-depth analysis of the relevant text and material context. Data were collected through literature study, observation, and interviews. The results showed that effective learning design requires teacher involvement in designing learning that is relevant to student needs, as well as being able to integrate educational technology and innovative learning strategies. In addition, this study also highlights the importance of developing a curriculum that is responsive to changing times and pays attention to the needs of individual students. Educator competencies that include material understanding, pedagogical skills, and managerial abilities are also key factors in ensuring the effectiveness of curriculum implementation. The findings of this research make an important contribution in enriching the understanding of how curriculum development, learning design, and educator competencies can support each other in improving the quality of education in the era of independent learning